Rational approximants of Pad\'e type of some class of double power series - Veselovska, G. M.; Golub, A. P.; Веселовська, Г. М.; Голуб, А. П. (Інститут математики НАН України, 2017)
Two--dimensional Pad\'e type approximants are constructed and studied for some special power series using method of generalized momentrepresentations.